If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -2z) + -2(4z + 6) = z + -8 (5 * 2 + -2z * 2) + -2(4z + 6) = z + -8 (10 + -4z) + -2(4z + 6) = z + -8 Reorder the terms: 10 + -4z + -2(6 + 4z) = z + -8 10 + -4z + (6 * -2 + 4z * -2) = z + -8 10 + -4z + (-12 + -8z) = z + -8 Reorder the terms: 10 + -12 + -4z + -8z = z + -8 Combine like terms: 10 + -12 = -2 -2 + -4z + -8z = z + -8 Combine like terms: -4z + -8z = -12z -2 + -12z = z + -8 Reorder the terms: -2 + -12z = -8 + z Solving -2 + -12z = -8 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -2 + -12z + -1z = -8 + z + -1z Combine like terms: -12z + -1z = -13z -2 + -13z = -8 + z + -1z Combine like terms: z + -1z = 0 -2 + -13z = -8 + 0 -2 + -13z = -8 Add '2' to each side of the equation. -2 + 2 + -13z = -8 + 2 Combine like terms: -2 + 2 = 0 0 + -13z = -8 + 2 -13z = -8 + 2 Combine like terms: -8 + 2 = -6 -13z = -6 Divide each side by '-13'. z = 0.4615384615 Simplifying z = 0.4615384615
| -2(7k+4)+9=32 | | (-8)x(6)= | | (j-3)j+4+j=196 | | 16x+11x=y | | x^2=16-28 | | 7v+6-3v=2 | | 5x+2=7x-48 | | 5(x+6x)=40(3-4x) | | 3(2r+1)=26+6r | | 10-20x+x=9x-33 | | -12/7+x=48/7 | | (5)x(-2)= | | 20x+x=180 | | 2b+11=-15 | | -8=-10-2 | | 3x^2+4=2x^2+4 | | -7-(3n+6)=-4-6n | | 15-20y+14y=15-35y | | 2(y+8)=32 | | -5(8n+6)+8(-3-n)=-54 | | 211=11x+13(19-x) | | 4+5b-5b=4 | | 35=7b | | 8(1y-5)=6y-18 | | 7x-19=-54 | | -2(4+7m)+6(4m-1)=-4 | | -7+12=-45 | | 2b-6=x | | 97=-7(1-7b)+3b | | -4(x+2y)-8(2x-4)= | | 24=-6(4b-7) | | -32-(54)= |